Playing to play: a piano-based user interface for music education video-games - Micheloni, Edoardo; Tramarin, Marco; Rodà, Antonio; Chiaravalli, Federico (Multimedia tools and applications, 2019)
This paper presents and discusses a case-study where a video-game is the means through which the user is induced to learn to use a complex and not-intuitive control interface such as the keyboard of a piano. The interaction paradigm is based on the idea, common to the Tangible Interfaces, to employ everyday objects, or anyway not designed for video games, as control user interface. In this research, the case study is the video game called Musa , in which players are led into an imaginary world where music is magic and every action is carried out through it. Combined with an educational path, this is thought to make players able to learn and, in a successive moment, to abstract this knowledge from the game, just by playing. Musa was evaluated in an experimental setup with 51 kids between 6 and 11 years old. Results show that subjects are able to improve their knowledge of the piano keyboard after two sessions of game and no significant differences were found between children with pre-acquired knowledge of the keyboard and the others.